IbM MGMP Matematika Kabupaten Batang - Nizaruddin Nizaruddin; Heni Purwati; Muhammad Prayito; Yanuar Hery Murtianto; Aurora Nur Aini (Pelita: Jurnal Pengabdian kepada Masyarakat, 2021)
Regulation of the Minister of State for the Utilization of State Apparatus and Bureaucratic Reform (Permen PAN & RB) Number 16 of 2009 concerning the Functional Position of Teachers, who wish to advance to rank III-b and above, are obliged to write papers. This regulation is imposed on teachers for promotion as evidence of professionalism in their duties and has an impact on mathematics teachers in Batang District. Batang District has 646 teachers who teach at SMK and 399 teachers who teach in SMA (BPS, 2014). The problems faced by partners are that teachers do not have the same perception about the standard of writing scientific papers in the form of Classroom Action Research, teachers are not active in classroom action research and teachers still have difficulty making articles and publishing them in relevant seminars or journals. The methods of implementing the activities of the IbM PTK Guru District of Batang are: lectures, group discussions and mentoring. The final output that is the target of this IbM is the PTK outline produced by the teacher participating in the activity. The CAR training activities for teachers at SMK Batang Regency were carried out well. Participants are happy with the CAR training that has been implemented. Most of these CAR training activities have two obstacles, namely in the form of extracting ideas and reviewing relevant research that can be overcome with mentoring. Constraints in the form of extracting ideas that are difficult to overcome can be overcome by recalling the various interesting cooperative learning models such as jigsaw, TGT, NHT and others. While the obstacle in the form of relevant research studies is overcome by introducing journals that have been published at PGRI University in Semarang as one of the references. Then the participants look for the appropriate articles so they can be cited.